2020
DOI: 10.1021/acs.bioconjchem.9b00847
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gold Nanoparticles with Different Surface Charges on Localization and Monocyte Behavior

Abstract: The use of gold nanoparticles (AuNP) has been established in nanocarriers, diagnostics, and biosensors. Access to the targeted sites of these nanomaterials could directly involve the first line of defense, the innate immune system. Charges of nanomaterials play a critical role in a number of aspects such as stabilization, cellular uptake, modulation, and function of cells. Interactions and modulations of the charged nanomaterials against the innate immune system may occur even at very low concentration. To und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 49 publications
(78 reference statements)
0
23
0
Order By: Relevance
“…Inorganic nanoparticles can be engineered to possess physiochemical properties for specific applications, e.g., their shape [17] and size [18] can be tuned to define nanoparticle properties. The molecular recognition properties of these particles are dictated by the chemical structure of the coating ligands, which form self-organized and multivalent binding sites for the guest species [19], a feature crucial for nanoparticle colloidal stability [20,21]. The surface of the nanoparticles interfaces with the external environment, and appropriately engineered surfaces can be used to regulate interactions between nanoparticles and biomolecules [22][23][24] driven by non-covalent interactions [9,25].…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic nanoparticles can be engineered to possess physiochemical properties for specific applications, e.g., their shape [17] and size [18] can be tuned to define nanoparticle properties. The molecular recognition properties of these particles are dictated by the chemical structure of the coating ligands, which form self-organized and multivalent binding sites for the guest species [19], a feature crucial for nanoparticle colloidal stability [20,21]. The surface of the nanoparticles interfaces with the external environment, and appropriately engineered surfaces can be used to regulate interactions between nanoparticles and biomolecules [22][23][24] driven by non-covalent interactions [9,25].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Yan et al (2008) reported that in contrast to neutral liposomes, cationic liposomes produce ROS inside DCs and this ROS is further required for ERK and p38 activation as well as induction of downstream cytokines, chemokines, and co-stimulatory molecules. Recently, Srijampa et al (2020) demonstrated that positively charged GNPs exhibited a high potential to induce immune responses (induce both proinflammatory, IL-1β and anti-inflammatory, TGF-β cytokine expression) as compared to negatively charged GNPs (induce only pro-inflammatory, TNF-α cytokine expression) in human monocyte cells. Although cationic NPs are suitable for cellular internalization through electrostatic interaction but sometime cationic NPs can cause platelet aggregation and hemolysis or can disturb membrane integrity.…”
Section: Surface Chargementioning
confidence: 99%
“…Although generally described as biocompatible, gold nanoparticles can, in some cases, elicit an immune reaction and it is thus essential to evaluate cellular responses such as cytokine or reactive oxygen species (ROS) production, an overlooked aspect in many reports. For instance, Srijampa and co-workers showed that the surface charge of gold nanoparticles determined whether pro-inflammatory cytokine production is increased or decreased [59,60]. However, other physical and chemical properties of the nanoformulations, such as size and hydrophobicity of the particle coating, may also be responsible for causing cytotoxicity, influencing compatibility with cellular immune responses such as transport processes or cellular damage [60].…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…For instance, Srijampa and co-workers showed that the surface charge of gold nanoparticles determined whether pro-inflammatory cytokine production is increased or decreased [59,60]. However, other physical and chemical properties of the nanoformulations, such as size and hydrophobicity of the particle coating, may also be responsible for causing cytotoxicity, influencing compatibility with cellular immune responses such as transport processes or cellular damage [60]. In this way, the design of nanoparticles for biomedical applications should respect these key aspects as well as the final objective and type of application.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%